Airport management strategies in recovery the air flight disruption: the case in the Lisbon Humberto Delgado airport - Carvalho, Carla Patrícia Nobre Marques (2019)
Airport disruption is a common situation and is expected to happen from time to time which can result from external and internal situations/factor. This dissertation aims to analyze the perception of passengers regarding disruption situations in the Lisbon Humberto Delgado Airport and to propose strategies and actions undertaken by the airport and the airline companies to improve the passenger experience and customer/passenger satisfaction. If disruption is foreseen to happen, in certain situations/factors, it can be predicted and planned/corrected in advance to diminish its effects. Also, when a disruption situation arises, the management process that is developed to provide a high level of satisfaction for the passengers is quite complex and challenging for the airport operator. Even so, the airport operator only has partial control of all the processes that make up the final offered service or product. The main research questions guiding this study are: aren’t passengers expecting from the airport management mechanisms to prevent this kind of situations? How can the airport improve passengers experience and offer customer value at the same time in a situation of disruption? A combined qualitative (personal deep interview with the Lisbon Airport Deputy Director and the Lisbon Hub Manager from the Portuguese flag company – TAP) and quantitative methodology (survey addressed to the passengers that used the Airport LHD in the summer of 2018, where 471 questionnaires were accepted). By analysing the obtained results, it was possible to demonstrate that the causes of disruption affect the level of satisfaction of the passengers as well as the actions taken by the airport and the airline. The level of information (high or low) that the passengers receive causes their level of satisfaction or unsatisfaction to increase or decrease with the operators.